2020
DOI: 10.1111/tbed.13891
|View full text |Cite
|
Sign up to set email alerts
|

Can domestic pigeon be a potential carrier of zoonoticSalmonella?

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
(86 reference statements)
1
14
0
1
Order By: Relevance
“…Although the great majority of our wildlife ST128 isolates were pan-susceptible (14/15, 93.3%), we predicted a plasmid featuring three mobile AMR genes ( bla TEM-1 , dfrA1 and sul2 ) in one pigeon isolate from 2020. The occurrence of bla TEM-1 and sul1 / sul2 has been observed previously in S. Typhimurium isolates from pigeons in Poland [ 60 ] and Egypt [ 61 ].…”
Section: Discussionsupporting
confidence: 55%
“…Although the great majority of our wildlife ST128 isolates were pan-susceptible (14/15, 93.3%), we predicted a plasmid featuring three mobile AMR genes ( bla TEM-1 , dfrA1 and sul2 ) in one pigeon isolate from 2020. The occurrence of bla TEM-1 and sul1 / sul2 has been observed previously in S. Typhimurium isolates from pigeons in Poland [ 60 ] and Egypt [ 61 ].…”
Section: Discussionsupporting
confidence: 55%
“…Choleraesuis, positive isolates scored positive for only one of the searched aminoglycosides resistance genes [ 47 , 48 ]. tetA was confirmed as the more frequent tetracycline resistance gene present among Salmonella [ 47 , 49 , 50 ]. Presence of bla TEM explained the resistance to Ampicillin in all but 2 resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…No amplification was obtained for sulI, tetR and bla CARB-2 genes in any of the isolates (Table 4). Kaczorek-Lukowska et al (2020) reported that tetA gene was among the most common antibiotic resistance genes that were isolated from domestic pigeons. Extensive use of tetracycline could have contributed to the selection of isolates with tetA gene.…”
Section: Resultsmentioning
confidence: 99%